Students' Exploration of Elective Courses in Flexible Higher Education: Findings From a Digital Simulation Task - van Brussel, Suzan; Smarius, Johan; Heikkinen, Sami; van der Stappen, Esther (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Flexible higher education requires students to compose individual learning routes by selecting elective courses. Such choice-making processes can induce stress and procrastination and thus demand effective guidance. This exploratory mixed-method study examines the students’ use of a digital tool to support them during exploration-in-breadth, the initial phase of educational choice-making processes. Bachelor students (n = 49) used a prototype that enabled browsing, filtering, and shortlisting electives. Trace log data and sequence analysis captured interaction patterns, including time-on-task, filter use, and selection behaviour, while a survey assessed motives, usability, and support needs. Results show that students display diverse navigation behaviour and that such a tool can facilitate structured exploration, particularly through filtering before shortlisting favourites. Students valued the tool for orientation but indicated the need for personal guidance when making final decisions. These findings support the potential for integrating asynchronous digital exploration with synchronous mentoring (blended guidance). Design implications include adaptive technological support, integration of mentor dialogue, and explicit development of students’ choice-making competencies.